The role of technology adopted by Agricultural Marketing Cooperative Society (AMCOS) on performance of grapevine farmers in Tanzania - Fatuma Ndauka; Salum Matotola (Cogent Business & Management, 2023)
This paper examines the roles of technology adopted by AMCOS and its influence on performance of farmers under CHABUMA and UWAZAMAM AMCOS in Dodoma Tanzania. The study adopted a cross-sectional research design and performance was measured by considering the Return on Investment (ROI) and profit. The survey method was employed, and a questionnaire tool was adopted for data collection from 167 grapevine farmers from CHABUMA and UWAZAMAM AMCOS. Results revealed that there is a significant influence of technology adopted on performance of farmers at a 5% level of significance (p < 0.05), especially in the aspect of availability, accessibility, and utilization. However, in regression analysis, availability of technology significantly and negatively influences the performance of farmers thus, as the farmers failed to have adequate technology their performance will not be improved. Nevertheless, the utilization and accessibility of technology influence positively the performance of farmers and mostly occurred by considering aggregate results than individual cases. Hence once the technology is available, utilized, and accessible to farmers, their performance will be improved. Inclusion of technology in grapevine production resulting to improved performance of farmers. This study contributes to the inclusion of technology on grapevine production from preparation up to the post-harvest stages whereby performance of farmers will be improved.
Keywords: 650; AMCOS; grapevine; performance; technology